Gastric rupture after bag-mask-ventilation. (2015) - Bednarz, Stephan; Filipovic, Miodrag; Schoch, Otto; Mauermann, Eckhard
Abstract: A 42 year old woman underwent bronchoscopy with procedural propofol sedation. During the procedure, the patient suffered respiratory arrest, and bag-mask ventilation was initiated. During forced mask ventilation, abdominal distention occurred. Even after correct placement of an endotracheal and a nasogastric tube, high inspiratory pressures persisted. The abdominal CT scan revealed a high amount of intraperitoneal free air. An emergent laparotomy confirmed a stomach rupture. Immediately after opening of the peritoneal cavity, peak ventilatory pressures decreased. In this case forceful bag-mask ventilation led to air insufflation into the stomach, increasing gastric pressure, and consecutive stomach rupture.